Relationship Between Cracks and Structure Settlement on Residential Building at Ayer Hitam - Che Manaf, Nor Syahidah; Tuan Chik, Tuan Norhayati (Recent Trends in Civil Engineering and Built Environment, 2023)
Building construction on soft soil including on peat has many challenges and difficulties. Building cracks and soil settlement are the most frequent issue in any area surrounded by peat soil. Therefore, this study is conducted to determine the effect and types of cracking which might be influenced by soil settlement together to propose the relationship between cracking and settlement. The location of the study being carried out in a residential building at Kompleks Penghulu Mukim Ayer Hitam, Muar. The visual inspection technique using specific measuring equipment such as taper gauge (measure crack) and triangle ruler (measure settlement) will be used to gain the data in conducting observation to the building. The building inspections were divided into two parts; the first part covers the investigation into measuring cracks, and the second part covers the investigation into measuring soil settlement. The length and width of the cracks were noted at the beginning of the study and monitoring activities were carried out on a regular basis to check whether these two parameters grew over time or not. A new formulation will be made to check on those parameters either directly proportional or not. A new formulation will be made to check on those parameters either directly proportional or not. Therefore, preventive measures can be set forth to avoid repetitive structural problems in the Ayer Hitam, Muar area in years to come. The results of the study found that the two parameters do not show a change directly proportional with time to each other but have proven the theory that cracking will only occur if there is a change in settlement.